2020
DOI: 10.14336/ad.2019.0521
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Physiological Links Between Physical Frailty and Cognitive Decline

Abstract: Declines in both physical and cognitive function are associated with increasing age. Understanding the physiological link between physical frailty and cognitive decline may allow us to develop interventions that prevent and treat both conditions. Although there is significant epidemiological evidence linking physical frailty to cognitive decline, a complete understanding of the underpinning biological basis of the two disorders remains fragmented. This narrative review discusses insights into the potential rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 182 publications
(184 reference statements)
0
63
0
3
Order By: Relevance
“…This extended life should grow in parallel with an increased disease-free lifespan (health span); therefore, policies that can support healthy ageing are necessary [3,4]. Increasing age is associated with declines in both cognitive and physical function [5]. Cognitive function and functional capacity are major determinants of quality of life in the elderly, and a reduction in these two factors may affect their ability to carry out activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This extended life should grow in parallel with an increased disease-free lifespan (health span); therefore, policies that can support healthy ageing are necessary [3,4]. Increasing age is associated with declines in both cognitive and physical function [5]. Cognitive function and functional capacity are major determinants of quality of life in the elderly, and a reduction in these two factors may affect their ability to carry out activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive function and functional capacity are major determinants of quality of life in the elderly, and a reduction in these two factors may affect their ability to carry out activities of daily living. There is a close link between physical frailty and cognitive decline with respect to their major underlying mechanisms, such as chronic inflammation, oxidative stress and neuroendocrine dysfunction [5]. Therefore, strategies that can slow the age-related decline of these functions are needed to prevent severe cognitive impairment and functional inability, and to help older adults maintain adequate performance status and independence, thus approaching the goal of healthy ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Dysarthria in Parkinson's disease (PD), which is a progressive neurodegenerative disease characterized by progressive loss of dopaminergic neurons in the substantia nigra, is universal [1][2][3][4][5][6][7][8]. It was indicated that almost 89% of patients with PD developed dysarthria [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Neurological diseases can manifest a series of symptoms due to abnormalities in nerve structure, biochemistry, or electrophysiology in the brain, spinal cord, or other nerve ( 6 ). Most of them are characterized by progressive neurodegeneration and injury closely related to aging, including PD, Alzheimer's disease (AD), amyotrophic lateral sclerosis, et cetera.…”
Section: Discussionmentioning
confidence: 99%
“…PD is a complex and slowly progressive neurodegenerative disease associated with multiple risk factors ( 5 ). Age and gender, environmental and behavioral factors, and other disease factors (i.e., sleep disturbances, hypertension, and traumatic brain injury) have been shown to be increased risk factors for the development of PD ( 5 , 6 ). These risk factors are not only crucial to the early diagnosis of PD but also helpful in the development of effective neuroprotection and health care strategies for appropriate populations at risk for PD ( 5 , 7 ).…”
Section: Introductionmentioning
confidence: 99%